LAJU INFILTRASI DAERAH BEKAS TAMBANG YANG DIPENGARUHI KARAKTERISTIK SIFAT FISIK TANAH - Himmes Fitra Yuda; Mohammad Apriniyadi; Suherman Dwi Nuryana; Novi Triany; Muhammad Adimas Amri; Murni Sulastri (JURNAL GEOGRAFI, 2022)
Infiltration is the process of entering water into the soil, infiltration capacity is the ability of the soil to absorb water per unit time. This study aims to determine the path of infiltration in the process of groundwater formation. This research was conducted in the Rumpin area, Bogor Regency, West Java Province. The method used in this study was carried out in two ways including collecting secondary data and primary data. Secondary data in the form of slope maps, rainfall maps. Primary data obtained from the results of field mapping (survey) and geology. The two data are correlated using the Geographic Information system so as to produce a map of the infiltration rate which has one unit which is sufficient, the soil type map, namely sand with poor gradation, the MAT map has three units, namely low, medium, adequate, the slope map has five units, namely very steep, steep, rather steep, sloping, flat, rainfall maps have one unit, namely height.